Antidiabetic Activity of Ethanol Extract of Red Castor Roots (Jatropha gossypiifolia L.) in White Wistar Rats Induced by Alloxan - Putri, Annisa Nur Lathifah Amanda; Haryoto, Haryoto (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Diabetes mellitus is a metabolic disorder indicated by high blood glucose levels. Red castor is a plant that has potential in the treatment of diabetes mellitus. This study aims to measure the impact of ethanol extract from the roots of the red castor plant (Jatropha gossypiifolia L.) in reducing blood glucose levels in male white Wistar rats that have been induced with alloxan at a dose of 150 mg/kgBW. The study used 25 male mice divided into 5 treatment groups. The negative control group was given distilled water as a substitute for the substance being tested, while the positive control group was given a dose of glibenclamide of 5 mg/kgBW. Apart from that, there were 3 treatment groups that were given extract from red castor root at doses of 25, 50 and 100 mg/kgBW respectively. Treatment was given for 14 days. Alloxan 150 mg/kgBW was used so that mice experienced an increase in blood glucose levels exceeding 200 mg/dL. The results of decreasing blood glucose levels respectively at doses of 25, 50, and 100 mg/kgBW were 101.0 mg/dL, 81.6 mg/dL, and 79.4 mg/dL. The percentage reduction in blood glucose levels obtained at doses of 25, 50, and 100 mg/kgBB was 73.63%, 77.89%, and 80.10%. Based on the results of statistical tests, the effect of using ethanol extract of red castor root at doses of 25 mg/kgBB, 50 mg/kgBB, and 100 mg/kgBB is comparable to using 5 mg/kgBB glibenclamide